Psychological Therapies in Patients with Irritable Bowel Syndrome: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Osama Altayar; Varun Sharma; Larry J. Prokop; Amit Sood; Mohammad Hassan Murad (Gastroenterology Research and Practice)
Background. Irritable bowel syndrome (IBS) is a poorly understood disease with few effective treatments. Psychosocial factors are believed to contribute to the pathogenesis of IBS. Objective. To evaluate the evidence for psychological therapies in IBS treatment. Methods. We searched six medical databases through February 6, 2014, for randomized controlled trials (RCTs) of psychological therapies for the treatment of IBS. Two independent reviewers identified the RCTs, extracted the data, and assessed trial quality. We used the random-effect model to pool standardized mean difference (SMD) and 95% confidence interval (CI) across trials. Results. 15 RCTs that mostly evaluated cognitive behavioral therapy were included. Psychological therapies were associated with improvement in IBS symptoms severity scales (SMD −0.618; 95% CI: −0.853 to −0.383), IBS-Quality of Life (SMD 0.604; 95% CI: 0.440 to 0.768), and abdominal pain (SMD −0.282; 95% CI: −0.562 to −0.001). No statistically significant effect was observed on diarrhea or constipation. Limitations. The trials were at increased risk of bias and the overall sample size was small leading to imprecision. Conclusion. Psychological therapies may improve the quality of life and symptom severity in IBS. The effect size noted is moderate to large and is clinically meaningful.